2012
DOI: 10.1016/j.jvs.2012.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Open and laparoscopic treatment of median arcuate ligament syndrome

Abstract: The available evidence demonstrates that both laparoscopic and open ligament release, celiac ganglionectomy, and celiac artery revascularization may provide sustained symptom relief in the majority of patients diagnosed with MALS. The role of arterial revascularization following ligament release remains unclear. The rate of open conversion with the laparoscopic approach is high, but no perioperative deaths have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
167
3
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(191 citation statements)
references
References 20 publications
2
167
3
5
Order By: Relevance
“…In our patients, postprandial abdominal pain was the most prominent symptom, consistent with the findings by Jimenez et al, where the most commonly reported symptom in 80% of patients was abdominal pain. 6 No abdominal bruits were discernible on auscultation in either of our patients. Several previous cases have reported the transient relief of symptoms with MALS when the patients bring their knees up to their chest.…”
Section: Case Bmentioning
confidence: 46%
“…In our patients, postprandial abdominal pain was the most prominent symptom, consistent with the findings by Jimenez et al, where the most commonly reported symptom in 80% of patients was abdominal pain. 6 No abdominal bruits were discernible on auscultation in either of our patients. Several previous cases have reported the transient relief of symptoms with MALS when the patients bring their knees up to their chest.…”
Section: Case Bmentioning
confidence: 46%
“…Both procedures are safe and effective. No death has been reported as a postoperative complication and the percentage of patients with immediate symptomatic relief is 85% [17].…”
Section: Treatmentmentioning
confidence: 99%
“…Other examinations leading to diagnosis are: MR, Doppler ultrasound evaluating blood flow velocity in the celiac artery, and arteriography which is becoming less popular due to its invasive nature. Each of these examinations should be performed both during inspiration and expiration, as the largest compression of the median arcuate ligament occurs during deep expiration but is not always visible during the inspiration phase [17].…”
Section: Diagnosismentioning
confidence: 99%
“…Common symptoms of patients with MALS include weight loss, postprandial abdominal pain, nausea, and vomiting. According to a systemic review on MALS, 80% of patients present with abdominal pain and up to 48% of patients experience weight loss [11]. The physical exam is usually unremarkable other than the objective weight loss and an epigastric bruit that has been reported in 35% of patients with MALS [11].…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…According to a systemic review on MALS, 80% of patients present with abdominal pain and up to 48% of patients experience weight loss [11]. The physical exam is usually unremarkable other than the objective weight loss and an epigastric bruit that has been reported in 35% of patients with MALS [11]. A thorough investigation of common etiologies of abdominal pain and weight loss should be performed (Table 1), prior to diagnosing MALS.…”
Section: Clinical Evaluationmentioning
confidence: 99%